Central Florida Gardening Calendar - Sydney Park Brown (EDIS)
Apply horticultural oils in January. Plant caladium bulbs in March. Watch for thrips, scale, and mites in May. Plant palms in June and July. Calibrate your sprinklers in September. This 10-page fact sheet tells what to plant and what to do in your central Florida garden in each month of the year. Written by Sydney Park Brown, and published by the UF Department of Environmental Horticulture, April 2012.